The Relation between Total Quality and Tourist Marketing Mix and their Effect on Achieving Outstanding Performance: An Analytical Study of the Opinions for a Sample of Employees in the Department of Religious Tourism - Holy Abbas Shrine (Czech Journal of Multidisciplinary Innovations, 2024)
The present study aims at exploring the relationship between the three main variables, namely; the overall quality, marketing mix and outstanding performance. This is from the employees' views who are working in Department of Religious Tourism at the Holy Abbas Shrine in Karbala. The paper adopts descriptive and analytical method. In order to achieve the research objectives, (60) questionnaires have been distributed to a sample of employees of the Department of Religious Tourism - Holy Abbas Shrine in Karbala. The paper tries to validate three hypotheses what are the relation between total quality and tourist marketing mix , total quality and outstanding performance and the effect of tourist marketing mix on outstanding performance. After analyzing the results, it is confirmed that there is a positive correlation between these three axes of the study.